Implementasi Tahap Pembiasaan Gerakan Literasi Sekolah - Nurmala Sari Burhan; Nurchasanah Nurchasanah; Imam Agus Basuki (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: The purpose of this study is to describe the implementation of the school litersion movement in the Tanjung Redeb Elementary School. The schools selected in this study are SDN 002 Tanjung Redeb, SDN 004 Tanjung Redeb, and SDIT Ash-Shohwa because these elementary schools have implemented a school literacy movement policy. This research uses a qualitative research method of multi-site research. Data collected related to the implementation of the school literacy movement in the habituation stage. The data analysis technique starts with a single site data analysis followed by cross site data analysis. A single site analysis procedure is performed by presenting data, reducing data, and withdrawing conclusions. Cross-site analysis procedures are carried out by looking for temporary cross-site findings. Research results can be reviewed from the focus of the study. Each site engages in literacy habituation by providing literacy facilities and infrastructure in the form of library facilities, reading corners in the school environment and in the classrooms and reading areas. At the stage of habituation, the selection of appropriate reading books for literacy is carried out, carrying out literacy before learning with reading and writing activities, making the school environment rich in text through pictures and posters, and involving the public in the implementation of school literacy.Abstrak: Tujuan penelitian ini untuk mendeskripsikan impementasi Gerakan Literasi Sekolah di Sekolah Dasar Tanjung Redeb. Sekolah yang dipilih dalam penelitian ini yaitu, SDN 002 Tanjung Redeb, SDN 004 Tanjung Redeb, dan SDIT Ash-Shohwa karena SD tersebut telah menerapkan kebijakan gerakan literasi sekolah. Penelitian ini menggunakan metode penelitian kualitatif jenis penelitian studi multisitus. Data yang dikumpulkan terkait implementasi gerakan literasi sekolah dalam tahap pembiasaan. Teknik analisis data dimulai dengan analisis data situs tunggal dilanjutkan dengan analisis data lintas situs. Prosedur analisis situs tunggal dilakukan dengan penyajian data, reduksi data, dan penarikkan kesimpulan. Prosedur analisis lintas situs dilakukan dengan mencari temuan sementara lintas situs. Hasil penelitian dapat ditinjau dari fokus penelitian. Setiap situs melakukan keggiatan pembiasaan literasi dengan dengan menyediakan sarana dan prasarana literasi berupa fasilitas perpustakaan, pojok baca di lingkungan sekolah dan di dalam kelas serta area baca. Pada tahap pembiasaan dilakukan kegiatan pemilihan buku bacaan yang tepat untuk literasi, melaksanakan literasi sebelum pembelajaran dengan kegiatan membaca dan menulis, membuat lingkungan sekolah kaya akan teks melalui gambar dan poster, dan melibatkan publik dalam  pelaksanaan literasi sekolah.